ЕВОЛЮЦІЯ НАУКОВИХ ПОГЛЯДІВ ЩОДО АЛЕЛОПАТИЧНОЇ АКТИВНОСТІ СІЛЬСЬКОГОСПОДАРСЬКИХ КУЛЬТУР У СІВОЗМІНАХ - Коваленко , Н.П. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2012)
Establishment and development of notions on allelopathic activity of plants in agrarian phytocoenosis are considered together with the evolution of scientific idea in works of national and foreign scientists. Analyses of peculiarities of research trends formation for chemical plant interaction and allelopathic soil fatigue in crop rotations with a different satiation with technical and forage grain-crops was carried out.